Early deaths in Jamaican children with sickle cell disease. - Rogers, D W (1978)
In Jamaican children with homozygous sickle cell (SS) disease diagnosed at birth two-year survival was 87%, compared with 95% in children with sickle cell-haemoglobin C (CS) disease, and 99% in normal controls. Death among those with SS disease occurred most often between the ages of 6 and 12 months. Principal causes were acute splenic sequestration and pneumococcal infection. Neonatal diagnosis of haemoglobinopathies must be followed by close observation if mortality is to be reduced by early diagnosis and treatment of these complications.